Nanoindentation and nano-scratching of hydroxyapatite coatings for resorbable magnesium alloy bone implant applications. (September 2022) - Lemoine, Patrick; Acheson, Jonathan; McKillop, Stephen; van den Beucken, Jeroen JJP.; Ward, Joanna; Boyd, Adrian; Meenan, Brian J.
Abstract: The corrosion rate of Mg alloys is currently too high for viable resorbable implant applications. One possible solution is to coat the alloy with a hydroxyapatite (HA) layer to slow the corrosion and promote bone growth. As such coatings can be under severe stresses during implant insertion, we present a nano-mechanical and nano-tribological investigation of RF-sputtered HA films on AZ31 Mg alloy substrates. EDX and XRD analysis indicate that as-deposited coatings are amorphous and Ca-deficient whereas rapid thermal annealing results in c-axis orientation and near-stoichiometric composition. Analysis of the nanoindentation data using a thin film model shows that annealing increases the coating's intrinsic hardness (H) and strain at break (H/E) values, from 2.7 GPa to 9.4 GPa and from 0.043 to 0.079, respectively. In addition, despite being rougher, the annealed samples display better wear resistance; a sign that the rapid thermal annealing does not compromise their interfacial strength and that these systems have potential for resorbable bone implant applications. Graphical abstract: Image 1 Highlights: We have successfully prepared RF-magnetron sputtered hydroxyapatite films on AZ31 Mg alloy substrate. As-deposited coatings are amorphous and Ca-deficient whereas annealed ones are c-axis oriented and stoichiometric. Annealing increases the coating's intrinsic hardness (H), strain at break (H/E) and wear resistance. The critical load is similar for all coatings, a sign that the annealing has not compromised their interfacial strength. Low temperature flash annealing of HA-coated Mg alloys enhances their potential as bone fracture fixation devices.